Prostate transmembrane androgen inducible protein 1 (PMEPA1): regulation and clinical implications - Zhu, Qicui; Wang, Yue; Liu, Yaqian; Yang, Xiaoke; Shuai, Zongwen (Frontiers in Oncology, 2023)
Prostate transmembrane androgen inducible protein 1 (PMEPA1) can promote or inhibit prostate cancer cell growth based on the cancer cell response to the androgen receptor (AR). Further, it can be upregulated by transforming growth factor (TGF), which downregulates transforming growth factor-β (TGF-β) signaling by interfering with R-Smad phosphorylation to facilitate TGF-β receptor degradation. Studies have indicated the increased expression of PMEPA1 in some solid tumors and its functioning as a regulator of multiple signaling pathways. This review highlights the multiple potential signaling pathways associated with PMEPA1 and the role of the PMEPA1 gene in regulating prognosis, including transcriptional regulation and epithelial mesenchymal transition (EMT). Moreover, the relevant implications in and outside tumors, for example, as a biomarker and its potential functions in lysosomes have also been discussed.